Community Empowerment to Increase Litopenaeus vannamei Productivity Towards Semi-Intensive System by Potential Analysis and Self-Feed Production - Sulastri Arsad; Muhammad Musa; Evellin Dewi Lusiana; Mohammad Mahmudi; Nanik Retno Buwono; Gatut Bintoro (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
Vaname shrimp is one of the leading cultivations of fishery production commodities in Indonesia which has high selling price and market share, also relatively resistant with high stocking density. Cultivation activities of this commodity can be carried out through three systems; namely traditional, semi-intensive, and intensive system. One group of cultivators who develop shrimp farming business is Mina Nusantara group in Lamongan District, where the cultivation system is still performed traditionally. The shrimp size was not uniform, and the survival rate was low once it harvested. Moreover, community empowerment was applied to increase vaname productivity towards semi-intensive system by culture potential analyses using SWOT and self-feed production training. Survey and experimental approach were used during the activities. The activities included survey and discussion with shrimp local farmer (Mina Nusantara), identified internal and external factors of culture by using SWOT analysis, carried out self-made artificial feed training, and program evaluation at the end. The activity resulted an increasing of farmer understanding of various culture system and they can produce the pellet in small scale by themselves. Based on SWOT analysis, the culture is potential to develop sustainably by regarding both internal and external factors.